PEDULILINDUNGI SEBAGAI SYARAT AKTIVITAS DI LUAR RUMAH DALAM MASA PANDEMI COVID-19 - Luh Suryatni (Fakultas Ilmu Komputer dan Desain - Unsurya, 2022)
Restrictions on activities by government policies bring the public to get to know more about the use of The Coronavirus Disease 2019 (COVID-19) has been the cause and responsible for many of deaths worldwide, which at this time of writing, the number of victims worldwide reached six million which 157 thousand deaths in Indonesia. Although preventive measures by Indonesia government such as Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) have been able to limit mortality and morbidity, the new mutations keep appearing and taking victims. The world considered vaccination to be a key to end the COVID-19 pandemic yet not little of public side eyes surrounding the development and the COVID-19 vaccine itself so local government decided to make vaccination as requirements people should obey. Indonesia government creating tracing and tracking application named PeduliLindungi as the tools and convenient way updating the latest information and surveillance the situation with the society which also included in the requirement for public to have access on public facilities.Â The purpose of this paper is to find out and analyzing PeduliLindungi as requirements for publik activities outside during the COVID-19 pandemic. The data collection method used is a literature study with descriptive analysis techniques. The results are showed that PeduliLindungi helping many including both society and government in increasing the number of vaccinated and a convenient tool for assuring society accessing public facilities during this still on-going pandemic. Â Key words: PeduliLindungi, vaccination, and COVID-19 pandemic.